Development and function of chicken XCR1+ conventional dendritic cells - Wu, Zhiguang; Shih, Barbara; Macdonald, Joni; Meunier, Dominique; Hogan, Kris; Chintoan-Uta, Cosmin; Gilhooley, Hazel; Hu, Tuanjun; Beltran, Mariana; Henderson, Neil C.; Sang, Helen M.; Stevens, Mark P.; et al. (Frontiers in Immunology, 2023)
Conventional dendritic cells (cDCs) are antigen-presenting cells (APCs) that play a central role in linking innate and adaptive immunity. cDCs have been well described in a number of different mammalian species, but remain poorly characterised in the chicken. In this study, we use previously described chicken cDC specific reagents, a novel gene-edited chicken line and single-cell RNA sequencing (scRNAseq) to characterise chicken splenic cDCs. In contrast to mammals, scRNAseq analysis indicates that the chicken spleen contains a single, chemokine receptor XCR1 expressing, cDC subset. By sexual maturity the XCR1+ cDC population is the most abundant mononuclear phagocyte cell subset in the chicken spleen. scRNAseq analysis revealed substantial heterogeneity within the chicken splenic XCR1+ cDC population. Immature MHC class II (MHCII)LOW XCR1+ cDCs expressed a range of viral resistance genes. Maturation to MHCIIHIGH XCR1+ cDCs was associated with reduced expression of anti-viral gene expression and increased expression of genes related to antigen presentation via the MHCII and cross-presentation pathways. To visualise and transiently ablate chicken XCR1+ cDCs in situ, we generated XCR1-iCaspase9-RFP chickens using a CRISPR-Cas9 knockin transgenesis approach to precisely edit the XCR1 locus, replacing the XCR1 coding region with genes for a fluorescent protein (TagRFP), and inducible Caspase 9. After inducible ablation, the chicken spleen is initially repopulated by immature CD1.1+ XCR1+ cDCs. XCR1+ cDCs are abundant in the splenic red pulp, in close association with CD8+ T-cells. Knockout of XCR1 prevented this clustering of cDCs with CD8+ T-cells. Taken together these data indicate a conserved role for chicken and mammalian XCR1+ cDCs in driving CD8+ T-cells responses.